Stem Cells and Cancer Stem Cells, Volume 6 Therapeutic Applications in Disease and Injury - Hayat, M.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
This book of the multi-volume series on stem cells and their cancerous counterparts features an in-depth explanation of the differences between pluripotent, multipotent and unipotent stem cell varieties. The specific types of stem cell singled out for discussion in this sixth volume include human mesenchymal, germ cell-derived pluripotent, induced pluripotent, human umbilical cord blood-derived, breast tumor, and hematopoietic stem cells. Human embryonic stem cells and their applications receive particular attention, with explanations of the process of embryoid body formation and the self-renewing capability of human embryogenic stem cells. Additional contributions examine the influence of TGF-beta on the propagation of human embryonic stem cells, and the mechanisms by which these cells differentiate into their four secondary incarnations, neurona, hepatocytes, cardiomyocytes, and retinal cells. With a clear exposition of donor policies for hematopoietic stem cells to complete the package, this sixth volume in the series will strengthen STEM$1 (Bs reputation for varied, yet comprehensive coverage of the topic.s
Keywords: Medicine; Oncology; Pathology; Transplantation of organs, tissues, etc; Stem cells; Biomedicine; Cancer Research; Stem Cells; Pathology; Transplant Surgery; Oncology